Refund Policy Due to Flight Cancellations Caused by the Covid-19 Pandemic: Consumer Protection Law’s Perspective - Huta Disyon; Kevin Bhaskara (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
The Covid-19 pandemic affects various aspects, including air transportation activities e.g., the Government of Indonesia has to impose travel restrictions to prevent the spread of the Covid-19 virus. In accordance with this policy, the airline canceled flights and issued travel vouchers for reimbursements. This study aims to analyse the refunds by airlines to airplane passengers because of flight cancellations due to the Covid-19 pandemic, as an impact of Government policies in perspective of the Consumer Protection Law. This research was conducted using a normative juridical method and the research specification is analytical-descriptive, because this article describes the implementation of the ticket refund by Garuda Indonesia (GIAA) to then be analysed to see if it has the potential to cause a violation of the Consumer Protection Law. The results showed that the implementation and handling of flight cancellations by rescheduling tickets and then refunding tickets by providing travel vouchers basically did not violate the provisions of laws and regulations in the field of aviation, and there were no violations of consumer rights. Furthermore, prospective passengers who experience financial losses can demand a refund in the form of cash to GIAA.